Comparing Seismic Performance of Steel Structures Equipped with Viscous Dampers and Lead Rubber Bearing Base Isolation under Near-Field Earthquake - Mohammad Ganji; Hossein Kazem (Civil Engineering Journal, 2017)
In the present research, seismic behaviours of a steel frame equipped with either viscous damper or lead-core rubber bearings (LRB) isolator were evaluated and compared under the effect of near-fault earthquake records. For this purpose, three buildings of 5, 10, and 15 stories equipped with lateral bearing systems composed of steel moment-resisting frames were subjected to 7 near-fault earthquake accelerogram pairs at earthquake hazard levels 1 and 2, so as to evaluate their responses under three scenarios, namely without any energy dissipation system, with viscous damper, and with LRB isolator, using dynamic analysis of time history utilizing PERFORM 3D v5 software. The results were indicative of enhancement in seismic performance of the viscous damper-equipped structures at earthquake hazard level 1, as the corresponding performance level was enhanced from life safety to uninterrupted usability, while no significant seismic performance level enhancement was determined at seismic level 2. Seismic isolator-equipped structures were also associated with seismic performance level enhancement from life safety to uninterrupted usability at both earthquake hazard levels. Relative lateral displacement at floor levels in damper-equipped structures and seismic isolator-installed buildings were found to be about 29% and 68% improved over that of the structure with no energy dissipation system. Results of distribution of shear forces within structures equipped with viscous damper and seismic isolator, as compared against that of the structures with no energy dissipation system, indicted increased and decreased shear forces, respectively..